Conditional Life Cycle: An Examination of Operating Performance for Leaders and Laggards - Cantrell, Brett W.; Dickinson, Victoria (Management Science, 2020)
The economics and management literature provides theoretical support for both leader and laggard firms to earn higher future operating returns. However, prior empirical research lacks a generalizable proxy to capture leader versus laggard behavior, thus limiting prior findings to specific contexts. This study utilizes a combination of firm-specific and industry life cycle identification to categorize leaders and laggards and validates the designation against constructs established in prior literature. Additionally, we examine each strategy’s effect on future performance, finding that, in general, laggards earn greater operating returns. Laggards gain their advantage through product differentiation—specifically, through marketing/advertising expenditures. Leaders are, on average, unable to convert their first movers’ advantage into sustainable future profitability once we control for other determinants of profitability. The leader/laggard classification using financial statement information has useful applications in analysis, forecasting, and valuation. This paper was accepted by Suraj Srinivasan, accounting.